2019
DOI: 10.1021/acsabm.9b00443
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modified Metallic Orthopedic Implant for Sustained Drug Release and Osteocompatibility

Abstract: Designing implants with good antibacterial activity and simultaneously providing a platform for osteoblast adhesion is a challenge for researchers. All metallic implants, currently in use, are biocompatible but bioinert. This may lead to a weak interface with the bone and cause asceptic loosening. The aim of the present study is designing an implant with good antibacterial activity and simultaneously providing a platform for osteoblast adhesion. This is achieved by surface engineering of the currently used met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…Antibiotics, known as a biologically functional molecule for killing bacteria, were severely restricted for the short-lasting effect and MDR in the clinic . Therefore, the long-term antibacterial assay of the hydrogels against S.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics, known as a biologically functional molecule for killing bacteria, were severely restricted for the short-lasting effect and MDR in the clinic . Therefore, the long-term antibacterial assay of the hydrogels against S.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Antibiotics, known as a biologically functional molecule for killing bacteria, were severely restricted for the short-lasting effect and MDR in the clinic. 51 Therefore, the long-term antibacterial assay of the hydrogels against S. aureus was tested in comparison to the PNC-NSR, a commonly used antibiotics (Figure S9). Both PTHP-gel and PNC-NSR have effectively killed the bacteria in the first 12 h, but several bacterial colonies emerged on the inhibited areas after culturing for another 12 h, meaning the antibiotic has worn off.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They confirmed that the coating has stronger antibacterial and osteogenic properties than bare Ti [ 82 ]. Other studies suggested that Ti-based implants coated with hydroxyapatite (HA)/chitosan (Chi) composite coating had good local sustained release Gent ability, excellent biocompatibility, and osseointegration [ 83 , 84 ]. However, in order to extend the life of these Ti-based implants in patients, they were often necessary to add various additional antibiotics to prevent bacterial infection.…”
Section: Local Drug Delivery Systems With Ti-based Implantsmentioning
confidence: 99%
“…Controllable micro/nano-rough Ti implant surfaces were prepared by anodic oxidation, hydrothermal treatment, etc ., introducing roughness, increased surface area, porosity, and improved wettability, which in turn could promote STI by enhancing adhesion, proliferation, and fibers secretion of soft-tissue cells. ,, However, single surface topographical alteration may not tackle the scenario that, after infection, the increased bacterial adhesion would compete with cell adhesion, thereby reducing the quality of STI. , Biofunctional coatings could be tailored toward specific cellular functions by immobilizing bioactive molecules onto the Ti implant surface to achieve STI augmentation . However, the drug-release rate of such biofunctional coating normally lacks control, and thus the coating would predispose to fail within a short period. , In our previous work, titania nanotubes (TNT) were prepared on pure Ti surfaces, and then cellular communication network factor 2 (CCN2) was loaded into TNTs by the lyophilization method to promote the biological response of fibroblasts . The CCN2-loaded TNT surface could promote fibroblast adhesion, viability, and actin cytoskeleton organization within 5 days, but the robust release of CCN2 in the first 15 min greatly reduced its long-term efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, the drug-release rate of such biofunctional coating normally lacks control, and thus the coating would predispose to fail within a short period. 21,22 In our previous work, titania nanotubes (TNT) were prepared on pure Ti surfaces, and then cellular communication network factor 2 (CCN2) was loaded into TNTs by the lyophilization method to promote the biological response of fibroblasts. 23 The CCN2-loaded TNT surface could promote fibroblast adhesion, viability, and actin cytoskeleton organization within 5 days, but the robust release of CCN2 in the first 15 min greatly reduced its long-term efficiency.…”
Section: Introductionmentioning
confidence: 99%